Middle English texts in transition : a festschrift dedicated to Toshiyuki Takamiya on his 70th birthday - Horobin, Simon; Mooney, Linne; Graham, Timothy (Woodbridge [England] : The University of York, 2014)
Fresh contributions to the study of medieval manuscripts, texts, and their creators.
Chaucer, Gower and Langland -- Lyrics and romances -- Devotional writings -- Owners and users of medieval books -- A tribute to Professor Takamiya.
Includes indexes.
Online resource; title from PDF title page (ebrary, viewed September 3, 2014).
JSTOR
Keywords: English literature -- Middle English, 1100-1500 -- History and criticism; Manuscripts, Latin (Medieval and modern); Littérature anglaise -- 1100-1500 (Moyen anglais) -- Histoire et critique; Manuscrits latins médiévaux et modernes; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; LITERARY CRITICISM -- Medieval; English literature -- Middle English; Manuscripts, Latin (Medieval and modern); 1100 - 1500; Geoffrey Chaucer; History of the Book; John Gower; Manuscripts; Middle English Texts; Nicholas Love; Walter Hilton; William Langland; Criticism, interpretation, etc